The Mnemonic Imagination - Keightley, E. author. aut Link
VIII, 239 p.
Keywords: An exploration of some of the key theoretical challenges and conceptual issues facing the emergent field of memory studies, from the relationship between experience and memory to the commercial exploitation of nostalgia, using the key concept of the mnemonic imagination.